Predictors of dropout in face‐to‐face and internet‐based cognitive‐behavioral therapy for bulimia nervosa in a randomized controlled trial. Issue 5 (12th November 2016) - Watson, Hunna J.; Levine, Michele D.; Zerwas, Stephanie C.; Hamer, Robert M.; Crosby, Ross D.; Sprecher, Caroline S.; O'Brien, Amy; Zimmer, Benjamin; Hofmeier, Sara M.; Kordy, Hans; Moessner, Markus; Peat, Christine M.; et al.
ABSTRACT: Objective: We sought to identify predictors and moderators of failure to engage (i.e., pretreatment attrition) and dropout in both Internet‐based and traditional face‐to‐face cognitive‐behavioral therapy (CBT) for bulimia nervosa. We also sought to determine if Internet‐based treatment reduced failure to engage and dropout. Method: Participants ( N  = 191, 98% female) were randomized to Internet‐based CBT (CBT4BN) or traditional face‐to‐face group CBT (CBTF2F). Sociodemographics, clinical history, eating disorder severity, comorbid psychopathology, health status and quality of life, personality and temperament, and treatment‐related factors were investigated as predictors. Results: Failure to engage was associated with lower perceived treatment credibility and expectancy (odds ratio [OR] = 0.91, 95% CI: 0.82, 0.97) and body mass index (BMI) (OR = 1.10; 95% CI: 1.03, 1.18). Dropout was predicted by not having a college degree (hazard ratio [HR] = 0.55; 95% CI: 0.37, 0.81), novelty seeking (HR = 1.02; 95% CI: 1.01, 1.03), previous CBT experience (HR = 1.77; 95% CI: 1.16, 2.71), and randomization to the individual's nonpreferred treatment format (HR = 1.95, 95% CI: 1.28, 2.96). Discussion: Those most at risk of failure to engage had a higher BMI and perceived treatment as less credible and less likely to succeed. Dropout was associated with less education, higher novelty seeking, previous CBT experience, and a mismatch between preferred and assigned treatment. Contrary to expectations, Internet‐based CBT did not reduce failure to engage or dropout. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:569–577)